Phase-transformation synthesis of Li codoped ZrO2: Eu3+ nanomaterials: Characterization, photocatalytic, luminescent behaviour and latent fingerprint development. Issue 7 (1st April 2021) - Renuka, L.; Anantharaju, K.S.; Gurushantha, K.; Nagabhushana, H.; Vidya, Y.S.; Suresh, C.; Sennappan, M.
Abstract: In recent years, key study was designing nanomaterials (NMs) with tunable properties in order to obtain high functional materials. For this purpose, an attempt with great effort has been put forward to synthesize ZrO2 :Eu:Li (1–11 mol%) NM with varying concentration of Li + ion that can have a control over phase, size, morphology, crystallinity, band gap and surface chemistry. More importantly, addition of Li as codopant influences the phase and crystallinity change with the change in concentration. However important challenges faced by this work was to understand the phase change, crystallinity, structural change and photocatalytic activity which has to be still explored. The synthesized NMs possess mixed phase and cubic phase with change in concentration of codopant which may be attributed to presence of defect states, micro strain, distortion of lattice. The energy band gap was found to decrease for 7 mol% NM attributed to the change in the phase. Porous morphology with variation in pore length was observed. Enhanced luminescence intensity with intense orange red emissions consistent to 5 D0 → 7 Fj (j = 0 to 4) intra configurational f-f transitions was observed for ZrO2 :Eu:Li + (1–11 mol%) nanophosphor excited at 394 nm. The visualization of latent fingerprints using ZrO2 : Eu: Li + 7mol% nanophosphor on several surfaces, the powder dusting technique was adopted. The enhanced fingerprint under UV light provides well resolved ridge patterns for the identification of individual latent finger prints using ZrO2 :Eu:Li (7 mol%) with clear resolution. Lower charge transfer resistance with enhanced photocatalytic activity for decolourization of Rhodamine B with high pore length to allow multiple reflections under UV light irradiation for 7 mol% NM with reduced band gap and optimum luminescence intensity was observed. Hence, the synthesized ZrO2 :Eu:Li (7 mol%) can be employed in forensic science towards latent fingerprint development, as a photocatalyst for environmental remediation and as luminescent material in display applications.